Coverage of pneumococcal, polio and rotavirus vaccines in Brazil: descriptive study, 2017 to 2020 - Neves, Rosália Garcia (2023)
Introduction: Recent years have been marked by a drop in vaccine coverage, creating a risk of outbreaks and epidemics of vaccine-preventable diseases. Objective: To describe the coverage of pneumococcal, polio and rotavirus vaccines from 2017 to 2020, in the regions and federative units (FUs). Methods: Descriptive study, with data from the Information System of the National Immunization Program. The vaccination coverage of each immunobiological agent was obtained according to the twenty-seven FUs, regions and whole Brazil, and the absolute differences in the coverage of each vaccine, from 2019 compared to 2020, were calculated. Results: In 2017 and 2020, respective coverage rates for pneumococcal vaccine were 92.2 and  81.0%, for polio vaccine 84.7 and 75.8% and for rotavirus vaccine 85.1 and 77.0%. The coverage of immunologicals showed an absolute difference of approximately 8 percentage points in the period between 2019 and 2020. No FU achieved adequate coverage for poliomyelitis and rotavirus. Conclusion: There was a drop in vaccination coverage between 2019 and 2020, with lower coverage for poliomyelitis, followed by rotavirus and pneumococcal disease, which may be related to the COVID-19 pandemic.